Untold health issue: computer vision syndrome / Mohd Fazil Jamaludin ... [et al.] - Jamaludin, Mohd Fazil; Saharan, Mohd Shafiz; Adzahar, Khairul Azfar (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2021)
Many of us have been impacted by the pandemic COVID-19. The pandemic outbreak has inspired many of us to contribute to educators' needs as they move towards online learning (Aguilar, 2020). Consequently, the usage of computers and other electronic devices that can be accessed for online learning and live classes has drastically increased. Due to increased duration of using these gadgets and electronic devices, many have experienced negative impacts to their health, particularly to their eyes. Gowrisankaran and Sheedy (2015) stated that symptoms reported by computer users include eye discomfort, low vision, headache, neck ache, and shoulder pain. Eye discomfort includes eye strain, eye fatigue, burning and irritation of the eyes, tired eyes, dry eyes, and the ache in and around the eyes. Most importantly, low vision comprises blurred vision at near and blurred vision when looking from close to far—all these syndromes known as computer vision syndrome (CVS).